Semiotic competencies for multimodal literacy in Spanish in Costa Rica’s high schools - Flores Solano, Carol (Innovaciones Educativas, 2020)
In response to the learning goals related to multimodal texts in the Costa Rican Spanish study program (MEP, 2017), and the lack of didactic proposals for its pedagogical treatment at a national level in secondary schools (Flores, 2019), this article’s purpose is to offer a series of semiotic competencies (Tobón, 2005) that will help in facilitating the multimodal teaching-learning process in the classroom. These competencies feed on the sociocognitive approach (Tobón, 2005), and the levels of creation of meaning in multimodal texts (Kress and Van Leeuwen, 2001; Kress, 2010) as well as on Bloom’s taxonomy for cognitive abilities (Talbert, 2019). As a result, they are presented as complex processes, for the approach, characterization, analysis, explanation, evaluation, and elaboration of multimodal texts, in specific sociocultural contexts and interactions. Based on the description of these competencies, the article condones the need to incorporate a semiotic dimension within the communicative competencies in the Spanish curriculum (MEP, 2017). It seeks to provide theoretical-methodological support to teachers to help them integrate the national curriculum’s objectives related to multimodal texts to the classroom. On a final note, this proposal offers a suggestion of studies regarding reading comprehension of multimodal texts, in order to update the national didactic and curricular processes, according to the development of multiple literacies at an international level (Anstey and Bull 2006; Cope and Kalantzis, 2009b; Blanchard and Farstrup 2011; Cooper et al., 2013; Reid and Comber 2004; Walsh 2010).